Antifungal activity of lactic acid bacteria against Aspergillus niger and Fusarium oxysporum - OUAZZANI, Houda; MAMI, Anas; MADJIDI, Nour Elhouda (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Many fungi are viewed as contaminants in nearly all food products. This contamination can be affected by various pollutants, including natural toxins. Among these toxins are mycotoxins produced by mold pathogens that affect plants. Combating these pathogens is essential in the agri-food industry, and the development of innovative strategies like biopreservation presents a promising solution. This study aims to isolate lactic acid bacteria (LAB) from fermented cow’s milk and examine their antifungal properties against Aspergillus niger and Fusarium oxysporum. The LAB were identified through morphological, biochemical, and MALDI-Tof analyses. Five strains of LAB sourced from fermented cow’s milk were evaluated for their antifungal activity using both the streak method and the double-layer method. The LAB isolates displayed inhibitory effects against Aspergillus niger and Fusarium oxysporum, showing a significant reduction in mean fungal diameter in comparison to the control, with these isolates categorizing under the Lactobacillus genus. The Fusarium oxysporum strain exhibited greater sensitivity to LAB compared to the Aspergillus niger strain. No decrease in antifungal activity was noted after subjecting the inhibitory metabolites in LAB supernatants to temperature treatments (4℃, 45℃, 60℃, and 100℃). After treatment with the proteolytic enzyme (chymotrypsin), no alterations in inhibition zones were observed. Inhibition was noted at an acidic pH for all strains. Investigating the nature of the inhibitory metabolites of LAB through thin-layer chromatography (TLC) and following their characterization allowed us to conclude that the antifungal properties of this LAB are attributed to the production of lactic and acetic acids. Article history: Received 15 January 2025; Revised 28 October 2025; Accepted 28 October 2025; Available online 20 December 2025